GRP per capita and hospital characteristics associated with intravenous tissue plasminogen activator adherence rate: evidence from the Chinese Stroke Center Alliance. Issue 3 (11th January 2021) - Zheng, Suxi; Lyu, Tian Jie; Li, Zixiao; Gu, Hongqiu; Yang, Xin; Wang, Chunjuan; Li, Hao; Jiang, Yong; Shen, Haipeng; Wang, Yongjun
Abstract : Background: Timely delivery of intravenous tissue plasminogen activator (IV-rt PA) is pivotal to eligible patients who had a stroke while achieving higher rates of IV-rt PA has been problematic. This paper focuses on investigating influential factors associated with the administration of IV-rt PA, primarily per capita gross regional product (GRP) and healthcare system factors. Methods: The study included 980 hospitals in the Chinese Stroke Center Alliance where 158 003 patients who had an acute ischaemic stroke received IV-rt PA between August 2015 and August 2019. The adherence rate to IV-rt PA within 4.5 hours time window in each hospital was the primary outcome. Influential factors were grouped into two categories: macroeconomic status and hospital characteristics. The outcome was analysed using multivariable linear regression. Results: GRP per capita (β=2.37, p<0.001), hospital stroke centre certification (β=3.77, p<0.001), number of neurologists (β=0.12, p<0.001), existence of emergency services for neurological treatment (β=7.43, p=0.014), presence of emergency department (β=10.03, p=0.019) and cooperating with emergency centre (β=4.65, p=0.029) were significantly positively associated with the adherence rate to IV-rt PA. Conclusions: Higher GRP per capita, affluent neurological personnel, well-equipped emergency services for neurological treatment and routine cooperation with the emergency centre were important for enhancing the adherence rate to IV-rt PA among patients who had an acute ischaemic stroke in China.